2018
DOI: 10.1111/dom.13232
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of diabetic retinopathy events associated with glucose‐lowering drugs in patients with type 2 diabetes mellitus: A network meta‐analysis

Abstract: Current evidence indicates that the association between DPP-4i, GLP-1RA or SGLT2 inhibitors and risk of DR remains uncertain in patients with T2DM. Some evidence suggests that sulfonylureas may be associated with increased risk of DR. However, given that DR events were not systematically assessed, these effects should be explored further in large-scale, well-designed studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 72 publications
2
42
0
Order By: Relevance
“…Since the time to metformin therapy to restore glycemic control following the diagnosis of T2DM is a critical factor in slowing DR progression, earlier introduction of metformin with DPP-4i seems to be appropriate. Evidence from a network meta-analysis suggests that treatment with sulfonylureas may be associated with an increased risk of DR [13]. Similarly, we found that sulfonylurea treatment was associated with a higher risk of developing NPDR (aHR 1.30, 95% CI 1.05-1.61).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Since the time to metformin therapy to restore glycemic control following the diagnosis of T2DM is a critical factor in slowing DR progression, earlier introduction of metformin with DPP-4i seems to be appropriate. Evidence from a network meta-analysis suggests that treatment with sulfonylureas may be associated with an increased risk of DR [13]. Similarly, we found that sulfonylurea treatment was associated with a higher risk of developing NPDR (aHR 1.30, 95% CI 1.05-1.61).…”
Section: Discussionsupporting
confidence: 69%
“…For example, a recent meta-analysis showed an increased risk of developing DR among subjects treated with sulfonylureas, compared to subjects receiving placebos. The effects of other antidiabetic drugs, such as thiazolidinediones, DPP-4i, glucagon-like peptide-1 receptor agonist (GLP-1RA), or sodium-glucose cotransporter 2 (SGLT2) inhibitors on the risk of developing DR, remain uncertain in patients with T2DM [13].…”
Section: Introductionmentioning
confidence: 99%
“…31 Finally, increased incidence of diabetic retinopathy-related events in the semaglutide arm could also be associated with the profound and rapid improvement of glycaemic control. 31 In contrast to previous meta-analyses, [32][33][34] Certain limitations should also be acknowledged. Almost none of the eligible studies were designed to assess microvascular endpoints, while our search identified a significant amount of potentially eligible records that did not report any data for the prespecified outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to previous meta‐analyses, we assessed renal microvascular complications utilizing outcomes used in clinical practice, such as UACR and eGFR, and extracted data both on diabetic retinopathy and its individual components (macular oedema, retinal detachment, retinal haemorrhage and vitreous haemorrhage) from a larger pool of trials that incorporate the most up‐to‐date evidence. Two meta‐analyses by Dicembrini et al and Garguilo et al were both based on evidence up to November 2016, therefore both miss numerous trials that have since explored the effect of GLP‐1 RAs on microvascular endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to NSAIDs, other systemic medications have been assessed in DR. Having the clinical perspective of a T2DM patient whose progression of the disease has reached development of DR, it is expected that these patients are already taking several medications whether for DM itself or related disorders from metabolic syndrome, like dyslipidemia or hypertension. A recent meta-analysis of glucose-lowering medications indicated an increased risk of DR with sulfonylureas, and there is no association with dipeptidyl peptidase 4 inhibitors (DPP-4i), glucagon-like peptide-1 receptor agonist (GLP-1RA), and sodium-glucose transport protein 2 (SGLT2); still, the latter was associated with the lowest probability to develop DR complications [229]. Regarding dyslipidemia, contradictive information has been found with its association to DR and its complication as shown from a meta-analysis that even though lipid profile was worse in patients who developed diabetic macular edema, no higher risk to develop a more severe stage nor worsening of hard exudates was shown [226].…”
Section: Designmentioning
confidence: 99%